PELAKSANAAN KUNJUNGAN ANTENATAL CARE (ANC) DI PUSKESMAS KALIJAGA KOTA CIREBON - Nurmala Sari; Ani Nurhaeni; Sumarni (LPPM ITEKES Mahardika, 2021)
Antenatal care is examination pregnancy in do for pregnant women during the her pregnancy to prevent complication of pregnancy and to prepare for a healthy birth. The purpose of this research conducted to determine the implementation of the antenatal care center Kalijaga Cirebon City in 2020. The kind of research use is descriptive survey. The population in research it is a whole pregnant women who performs the first visit in the work area Kalijaga Cirebon as many as 195 pregnant women with a sampleof 66 respondents. The instrument used in this study used a checklist. The research results show that pregnant women get the service measurement of the height bodies and weight as many as 60 (91%), the measurement of blood pressure 60 (91%), measurements the upper arm circumference 60 (91%), examinatin fundus uteri high 54 (82%), screening for TT immunization 47 (71%), administration of Fe tablets 39 (59%), percent the fetus and fetal heartbeat 33 (50%), a laboratory test of 43 (65%), managementof cases kasus 33 (50%) and a dialogue 60 (91%). Conclusion obtained in this research that there are pregnant women who should be given at the time of the first. Suggested health workers to improve services to pregnant women in accordance with the care of service standards that has been determined by the government.